The TORCH time-of-flight detector - Harnew, N; Brook, N; Castillo García, L; Cussans, D; Föhl, K; Forty, R; Frei, C; Gao, R; Gys, T; Piedigrossi, D; Rademacker, J; Ros Garcia, A; et al. (Elsevier, 2015)
The TORCH time-of-flight detector is being developed to provide particle identification between 2 and 10 GeV/c momentum over a flight distance of 10 m. TORCH is designed for large-area coverage, up to 30 m2, and has a DIRC-like construction. The goal is to achieve a 15 ps time-of-flight resolution per incident particle by combining arrival times from multiple Cherenkov photons produced within quartz radiator plates of 10 mm thickness. A four-year RandD programme is underway with an industrial partner (Photek, UK) to produce 53×53 mm2 Micro-Channel Plate (MCP) detectors for the TORCH application. The MCP-PMT will provide a timing accuracy of 40 ps per photon and it will have a lifetime of up to at least 5 Ccm-2 of integrated anode charge by utilizing an Atomic Layer Deposition (ALD) coating. The MCP will be read out using charge division with customised electronics incorporating the NINO chipset. Laboratory results on prototype MCPs are presented. The construction of a prototype TORCH module and its simulated performance are also described.